Iodine‐Catalyzed Ring Opening of 1, 1‐Diacylcyclopropanes for Synthesis of Fully Substituted Pyrazole Derivatives. Issue 25 (23rd June 2020) - Yang, Xiuqin; Zhu, Jin; Bao, Yishu; Ding, Ziyu; Yang, Fulai; Zhou, Qingfa; Chen, Ming
Abstract : An iodine‐catalyzed [3+2] cycloaddition/ring opening reaction of 1, 1‐diacylcyclopropanes with sulfonyl hydrazides has been reported. In the presence of 20 mol‐% iodine, a range of structurally diverse fully substituted pyrazoles with a hydroxy functional group are obtained in moderate to excellent yields with extremely high regioselectivity. Abstract : Iodine‐catalyzed ring opening of 1, 1‐diacylcyclopropanes for synthesis of fully substituted pyrazole derivatives have been reported. This reaction tolerates a broad range of cyclopropyl ketones and sulfonyl hydrazides to afford useful and densely functionalized pyrazole derivatives with a hydroxy functional group.